Cross-subject variability of the optic radiation anatomy in a cohort of 1065 healthy subjects. - Herlin, B.; Uszynski, I.; Chauvel, M.; Poupon, C.; Dupont, S. (Surgical & Radiologic Anatomy, 2023)
Introduction: Optic radiations are tracts of particular interest for neurosurgery, especially for temporal lobe resection, because their lesion is responsible for visual field defects. However, histological and MRI studies found a high inter-subject variability of the optic radiation anatomy, especially for their most rostral extent inside the Meyer's temporal loop. We aimed to better assess inter-subject anatomical variability of the optic radiations, in order to help to reduce the risk of postoperative visual field deficiencies. Methods: Using an advanced analysis pipeline relying on a whole-brain probabilistic tractography and fiber clustering, we processed the diffusion MRI data of the 1065 subjects of the HCP cohort. After registration in a common space, a cross-subject clustering on the whole cohort was performed to reconstruct the reference optic radiation bundle, from which all optic radiations were segmented on an individual scale. Results: We found a median distance between the rostral tip of the temporal pole and the rostral tip of the optic radiation of 29.2 mm (standard deviation: 2.1 mm) for the right side and 28.8 mm (standard deviation: 2.3 mm) for the left side. The difference between both hemispheres was statistically significant (p = 1.10–8). Conclusion: We demonstrated inter-individual variability of the anatomy of the optic radiations on a large-scale study, especially their rostral extension. In order to better guide neurosurgical procedures, we built a MNI-based reference atlas of the optic radiations that can be used for fast optic radiation reconstruction from any individual diffusion MRI tractography.